Pendampingan Kepatuhan dan Kesadaran Hukum Bagi Masyarakat Desa Dusun Sawah - Muhammad Azizzullah Ilyas; Muhammad Abudzar (Institut Agama Islam Negeri Bengkulu, 2020)
Legal Compliance Assistance aims to make citizens understand and behave according to norms; legal and personal documents that must be owned; Marriage Book, Birth Certificate, Family Card and Identity Card. This Legal Compliance Assistance is held for eight months starting from May to December took place in the village of Dawah Sawah. The target of Legal Compliance Assistance is the people of Dusun Sawah village who are married and aged 17 years and over. The results of this Legal Compliance Assistance change the insight, understanding and attitude towards the urgency and the existence of a Family Card, Marriage Book, Birth Certificate and Identity Card. The results were enumerated and mass-produced Family Card. Data Collection is carried out for those who do not have a Marriage Book and steps are taken so that the issue of Marriage Book issues that are constrained can be overcome immediately.